FEATURES OF THE PROGRESSION AND TREATMENT OF RESPIRATORY INFECTIONS IN CHILDREN WITH ALLERGIES - M. S. Savenkova; N. А. Abramova; А. D. Abramov (Вопросы современной педиатрии, 2014)
The article presents the literature data on the age characteristics of allergic reactions, their classification and clinical manifestations. The authors’ own data are given — the results from the examination of 143 families, including 120 children with frequent respiratory diseases (main group) and 23 children with occasional diseases (comparison group). It is shown that the incidence of allergic diseases in children in the main group and their parents is significantly superior to that in the control group. A clinical case of an allergic reaction in a child with a mixed intracellular infection is described. The principles of a macrolide therapy are stated.